PENINGKATAN KETERAMPILAN MENYIMAK TEKS PROSEDUR PADA SISWA KELAS VII DI SMPN 6 SINGINGI HILIR MELALUI STRATEGI GUIDED NOTE TAKING - Deliana Deliana (JURNAL PENDIDIKAN ROKANIA, 2020)
This study aims to improve the skills of listening to procedural texts in grade VII students at SMPN 6 Singingi Hilir through the Guided Note Taking strategy. This type of research is classroom action research using two cycles and four stages, namely planning, action, observation, and evaluation. Research instruments, namely teacher and student observation sheets and performance tests in the form of the results of the test of listening to the text of the procedure. The study revealed that the initial test results of the average value of students was 54.4, the first cycle the average value of students was 77.53 and in the second cycle the average value of listening to students was 90.3. Test results show an increase. From the results of the study revealed that the evaluation results indicate the success of teachers in learning is determined by planned activities with an improved change between the implementation of the activities of cycle I and II. It was concluded that learning to listen to the text of the procedure with the guided note taking strategy could improve the listening skills of the eighth grade students at SMPN 6 Singingi Hilir.